Topical Aspects of Distance Learning in General Secondary Education - Kazakeviča, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays education is the most important precondition for existence and development of society. In the world the information and communication technologies and their application in education develop more and more rapidly, encouraging the society to lifelong learning and building a knowledge society. To provide lifelong education in accordance with the interests of the people and concerns of regional socio-economic development, it is important to offer people a second-chance education that can be implemented through introducing distance learning in general secondary education in Latvia. Therefore, it is important to research the specificity of distance learning in general secondary education and to develop and implement distance learning programmes on the basis of theoretical knowledge. This article reveals that Liepaja Evening (shift) Secondary school is designing a distance learning programme with an emphasis on the support system, in which a great contribution is given by subject teachers, consultants, advisors and class teachers who help the students to orientate in the educational process and learning materials, and who encourage, support and motivate the students.